Interaction of Mycotoxins with α1-Acid Glycoprotein (AGP) and Bovine Milk Proteins: Zearalenone, Zearalenols, and Sterigmatocystin Form Highly Stable Complexes with AGP - Miklós Poór; Patrik Gömbös; András Szabó; Balázs Zoltán Zsidó; Csaba Hetényi; Tamás Huber; András Lukács; Sándor Kunsági-Máté (Toxins)
Mycotoxins are frequent food contaminants posing health risk to humans and animals. Since these interactions have been barely studied yet, we examined the potential complex formation of mycotoxins with human α1-acid glycoprotein (AGP) and with bovine milk proteins (including casein (CSN), β-lactoglobulin (LG), and α-lactalbumin (LA)) based on fluorescence spectroscopic and ultracentrifugation techniques. Only weak interactions (logK = 2.7 to 3.5) of certain mycotoxins were observed with CSN, LG, and/or LA. Ultracentrifugation experiments demonstrated that aflatoxin M1, zearalenone, and α-zearalenol form more stable complexes with CSN than with LG or LA. These mycotoxins bound to bovine serum albumin with more than a tenfold higher affinity compared to CSN; nevertheless, it has likely limited importance due to the relatively low levels of BSA in bovine milk. Zearalenone, zearalenols, and sterigmatocystin showed strong interactions with AGP (logK = 5.5 to 6.4), suggesting that AGP may play an important role in the plasma protein binding of these mycotoxins.